ZAPU’s diplomatic relations during the war of liberation from 1961 up to 1979. - Sibanda, Davis (Midlands State University, 2020)
This study focuses on ZAPU’s diplomatic relations during the war of liberation. It strives at capturing external players that were not well documented in the historical narratives of Zimbabwe’s history of liberation. The study traces the origins of ZAPU’s diplomatic relations and the impact of these diplomatic relations in the manner through which ZAPU became portrayed as an authentic liberation movement due to the ability to craft sophisticated soft power. The study further looks at the wide range of diplomatic assistance that ZAPU received from various sympathisers which the party had established intricate diplomatic relations with. The research also projects out the nature of ZAPU’s interactions with its allies at different phrases of liberation struggle. It also assesses the impact of diplomatic relations on the outcome of the liberation struggle. ZAPU’s diplomatic relations enabled the party to be equipped with weapons of mass destructions which were in commensurate with weapons of the enemy. ZAPU’s diplomatic relations strengthened its military wing ZPRA to partial invisibility which threatened Smith’s resistance to grant Africans their independence and eventual succumbed to the pressure as victory was becoming certain for guerrilla forces. ZAPU’s diplomatic relations also buttresses ZAPU’s genuine commitment to the liberation struggle which in many cases has been deliberate undermined so as to justify ZANU dominance and legitimize its leadership. The study demythologises such tailor made historical narratives on the liberation struggle and sheds light of a balanced representative history of the liberation struggle. ZAPU’s diplomatic relations with OAU and the Frontline States are also discussed as these bodies were extensively involved in the day to day politics of Zimbabwe’s liberation movements. The study will be constructed using both primary and secondary sources and a qualitative method will be used in writing of this thesis.